2020
DOI: 10.1080/02713683.2020.1737138
|View full text |Cite
|
Sign up to set email alerts
|

Interocular Symmetry of Foveal Cone Topography in Congenital Achromatopsia

Abstract: Purpose: To determine interocular symmetry of foveal cone topography in achromatopsia (ACHM) using non-confocal split-detection adaptive optics scanning light ophthalmoscopy (AOSLO).Methods: Split-detector AOSLO images of the foveal cone mosaic were acquired from both eyes of 26 subjects (mean age 24.3 years; range 8 -44 years, 14 females) with genetically confirmed CNGA3-or CNGB3-associated ACHM. Cones were identified within a manually delineated rod-free zone. Peak cone density (PCD) was determined using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
(61 reference statements)
1
18
0
Order By: Relevance
“…15,18,20,26,28,40 Moreover, interocular symmetry extends to the topography of the foveal cone mosaic as imaged with adaptive optics scanning light ophthalmoscopy. 16,41 Given the structural and functional symmetry, it can be assumed that both eyes in patients with ACHM have similar therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…15,18,20,26,28,40 Moreover, interocular symmetry extends to the topography of the foveal cone mosaic as imaged with adaptive optics scanning light ophthalmoscopy. 16,41 Given the structural and functional symmetry, it can be assumed that both eyes in patients with ACHM have similar therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Axial length was measured using a Zeiss IOL Master (Carl Zeiss Meditec, Jena, Germany) and used to scale AOSLO images as previously described. 26 AOSLO montages were manually aligned using Adobe Photoshop CS6 to infrared reflectance and en face SDOCT images using retinal vasculature. For intrapatient comparisons between visits, AOSLO montages were transformed to the same scale (µm/pixel).…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23][24] Marked variability in the cone mosaic has been observed across patients with ACHM. 23,[25][26][27][28] Nonconfocal split-detection AOSLO demonstrated that inner segment structure remained in these "dark spaces." The degree of remnant inner segment structure may be important for participant selection for gene therapy trials and could be used to identify patients most likely to benefit from cone-directed rescue.…”
Section: Introductionmentioning
confidence: 99%